Use of Colours in the Latvian Archaeological Textiles - Pigozne, Ieva (Archaeological Textiles Review, 2013)
The article contains a report of a research project on the colours used in the archaeological textiles of the 3rd-14th centuries AD in the areas of Latvia inhabited by the Baltic population. It concludes that dark blue was the most popular colour of the garments found in the burials of the wealty Baltic people. Blue and brown single yarns have been detected in the analysed fabrics, and blue, red, and yellow plied yarns have been distinguished in the decorations of the dress. Red and yellow were more frequently observed in female dress. Such a colour scheme seems to have been quite popular in the Baltic-inhabited areas of the Latvian territory in the 3rd-14th centuries AD.